(untitled) (Scientific journal of the Fergana State University, 2024)
To determine the composition of mountain minerals in the Fergana Valley, minerals were taken and analyzed from the mountains of the Besharyk region, the mountains of the Chodak village of the Pop district of the Namangan region and the mountains of the Yordon village of the Fergana region of the Fergana region. The result of a spectral-semi-quantitative analysis of the mineral composition (Au+25 elements) was determined on the Grand Potok atomic emission complex analyzer using the spill method and the following results were obtained.